Development of functional mathematical literacy of pupils with moderate special educational needs - Tomėnienė, Laima (Social Welfare: Interdisciplinary Approach, 2014)
The article deals with modelling of the system of functional mathematical literacy development of eighth form pupils with moderate special educational needs, learning in mainstream schools. Applying the action research method, the measurements of the participants of the (self-)educational process are analysed and, based on them, the possibilities of developing functional mathematical literacy of pupils with moderate SEN in the mainstream school, grounded on the approaches and ideas of pragmatism, social constructivism, social participation and empowerment theories, are revealed.